2014
DOI: 10.1007/s00442-014-2995-6
|View full text |Cite
|
Sign up to set email alerts
|

Plants respond to leaf vibrations caused by insect herbivore chewing

Abstract: Plant germination and growth can be influenced by sound, but the ecological significance of these responses is unclear. We asked whether acoustic energy generated by the feeding of insect herbivores was detected by plants. We report that the vibrations caused by insect feeding can elicit chemical defenses. Arabidopsis thaliana (L.) rosettes pre-treated with the vibrations caused by caterpillar feeding had higher levels of glucosinolate and anthocyanin defenses when subsequently fed upon by Pieris rapae (L.) ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
173
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(179 citation statements)
references
References 57 publications
5
173
0
1
Order By: Relevance
“…Plants thus seem to use overlapping signaling systems to respond to metabolic changes and biotic stress. Recent work showed that plants respond rapidly to even just the leaf vibrations caused by insect herbivores (Appel and Cocroft, 2014). Such a mechanical signal can travel much faster through the plant than, for example, phytohormones.…”
Section: Discussionmentioning
confidence: 99%
“…Plants thus seem to use overlapping signaling systems to respond to metabolic changes and biotic stress. Recent work showed that plants respond rapidly to even just the leaf vibrations caused by insect herbivores (Appel and Cocroft, 2014). Such a mechanical signal can travel much faster through the plant than, for example, phytohormones.…”
Section: Discussionmentioning
confidence: 99%
“…For example, tryptophan plays a critical role in regulating plant responses to biotic and abiotic stresses (Radwanski and Last, 1995; Zhao and Last, 1996; Sangha et al ., 2011). Transcript profiling data generally show herbivory‐induced changes in the expression of genes related to the production of glutamine, glutamic acid, asparagine and aspartic acid (Thompson and Goggin, 2006; Caldana et al ., 2011; Appel and Cocroft, 2014; Zhou et al ., 2015), which are involved in nitrogen assimilation (Coruzzi and Last, 2000). Amino acids also play a role in signal transduction to induce defence gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds play a very important role in plants by protecting them from herbivores and pathogens [Appel & Cocroft, 2014]. Glucosinolate breakdown products deliver health benefi ts also for humans.…”
Section: Introductionmentioning
confidence: 99%